PRAKTIK YANG TEPAT MENGHIDUPKAN HADIS LARANGAN MENGAMBIL GAMBAR PADA KEHIDUPAN - Putra Nabawi, Griya; OHZA IKMAYA SAFITRI; SETYOAJI; TIA FANIA (Aqwal: Journal of Qur'an and Hadis Studies, 2020)
This study aims to examine the proper practice of enforcing the ban on taking pictures in millennial life. especially the hadiths regarding the prohibition of taking pictures. The limitations of this research include the proper practice of turning on the ban on taking pictures in millennial life. The issues examined in this study are: (1) textual analysis of the hadith of the Prophet prohibiting drawing. (2) Contextual analysis of the hadith of the Prophet prohibiting drawing (3) Proper practice in reviving the hadith of the Prophet prohibiting drawing in the present. The conclusions of this study are (1) the hadith that we examined is a hadith that contains God's threat to painters, especially painters whose painting objects are animate creatures, (2) Scholars differ on what criteria will be affected by the threat. However, some opinions say that this threat only applies to painters whose work resembles God's creation, (3) taking pictures is an activity that is permissible, and it becomes something good if it has a positive impact. However, taking pictures can be illegal if the content created has a negative impact and also violates Islamic sharia provisions